Simulation and Comparison of AODV Variants under Different Mobility Models in MANETs - Garg, Shiwani (My University, 2016)
Today in the world of computer communications the concept of adhoc networking is at boom. Those users who wants to communicate with each other forms a temporary network in which the nodes acts both as host as well as router. Nodes are connected wirelessly that is free from any centralized administration. In these type of networks, nodes change their positions frequently. For this purpose, routing protocol is needed for MANETs. AODV (Ad-hoc On Demand Distance Vector) is a reactive routing protocol for MANETs and it enables multihop routing within the mobile nodes taking part in initiating and preserving an ad-hoc network. In multihop routing, route is requested only when it is required and it does not keep track of routes to the destination node. Primary idea of this paper is to assess the AODV variants underneath acquainted mobility models. We have proposed this analysis in MANETs(Mobile Adhoc Networks). We have considered three mobility conditions i.e. Group mobility model, RandomWaypoint and Manhattan model. In our paper, performance metrics like PDR (Packet delivery ratio), Throughput and End to End Delay are used to evaluate the performance of AODV variants. The performance metrics are examined with varying node density and Ns-2 is used as an network simulator to carry out these simulations. Keywords: AODV; AOMDV; MAODV; MANET; Mobility Models; PDR; Throughput. ii
Master of Engineering-CSE
Keywords: AODV; AOMDV; MANET; Mobility Models; PDR; Throughput